Limited Heme Oxygenase Contribution to Modulating the Severity of Salmonella enterica serovar Typhimurium Infection - Valentina P. Sebastián; Daniela Moreno-Tapia; Felipe Melo-González; María P. Hernández-Cáceres; Geraldyne A. Salazar; Catalina Pardo-Roa; Mónica A. Farías; Omar P. Vallejos; Bárbara M. Schultz; Eugenia Morselli; Manuel M. Álvarez-Lobos; Pablo A. González; et al. (MDPI AG, 2022)
An important virulence trait of Salmonella enterica serovar Typhimurium (S. Typhimurium) is the ability to avoid the host immune response, generating systemic and persistent infections. Host cells play a crucial role in bacterial clearance by expressing the enzyme heme oxygenase 1 (Hmox1), which catalyzes the degradation of heme groups into Fe2+, biliverdin, and carbon monoxide (CO). The role of Hmox1 activity during S. Typhimurium infection is not clear and previous studies have shown contradictory results. We evaluated the effect of pharmacologic modulation of Hmox1 in a mouse model of acute and persistent S. Typhimurium infection by administering the Hmox1 activity inductor cobalt protoporphyrin-IX (CoPP) or inhibitor tin protoporphyrin-IX (SnPP) before infection. To evaluate the molecular mechanism involved, we measured the colocalization of S. Typhimurium and autophagosome and lysosomal markers in macrophages. Administering CoPP reduced the bacterial burden in organs of mice 5 days post-infection, while SnPP-treated mice showed bacterial loads similar to vehicle-treated mice. Furthermore, CoPP reduced bacterial loads when administered after infection in macrophages in vitro and in a persistent infection model of S. Typhimurium in vivo, while tin protoporphyrin-IX (SnPP) treatment resulted in a bacterial burden similar to vehicle-treated controls. However, we did not observe significant differences in co-localization of green fluorescent protein (GFP)-labeled S. Typhimurium with the autophagic vesicles marker microtubule-associated protein 1A/1B-light chain 3 (LC3) and the lysosomal marker lysosomal-associated membrane protein 1 (LAMP-1) in macrophages treated with CoPP. Our results suggest that CoPP can enhance antimicrobial activity in response to Salmonella infection, reducing bacterial dissemination and persistence in mice, in a CO and autophagy- independent manner.